If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -9 + 9 = 9 Reorder the terms: -9 + 9 + y = 9 Combine like terms: -9 + 9 = 0 0 + y = 9 y = 9 Solving y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 9
| 11/10=x+1/2 | | w+7/10=27/10 | | 6+d=31/5 | | t+5/6=41/6 | | (x-3)*(x+4)=0 | | 6+11=-17-8x | | a-9/10=-3/20 | | n+6=23/4 | | m+9=49/5 | | w+8=25/3 | | 4/5+b=29/5 | | -4/7=b-4/7 | | n-5/7=-29/70 | | a-6=-25/4 | | w-10=-12 | | -5/3=t-8/9 | | d+1=4 | | x/3=12/2 | | x/3=12/3 | | 2/3+b=7/33 | | t-7/9=-1/36 | | a+9/10=-61/10 | | t/3=7 | | 35/4=k+3/4 | | a+6/7=90/7 | | w/2=7 | | t+1/8=-7/40 | | 1/10=x+2/5 | | 41/72=n+4/9 | | 10+w=14 | | 1+m=4/11 | | a-5=-45/11 |